Two‐Phase Rubber–Plastic Matrices’ Stabilization of Organic Room‐Temperature Phosphorescence Afterglows Better than Plastic Matrix - Junwu Chen; Yuefa Zhang; Shiguo Zhang; Guanyu Liu; Qikun Sun; Shanfeng Xue; Wenjun Yang (Small Structures, 2023)
The rigid yet polar polymers as matrices for organic‐doped room‐temperature phosphorescence (RTP) polymers are widely reported, but nonpolar rigid plastics such as polystyrene (PS) are thought to be ineffective matrix and rarely attempted. Herein, it is reported that PS–polyisoprene–PS (SIS) elastomer and rubber phase‐containing high‐impact PS (HIPS) can stabilize brighter and longer‐lived organic RTP than PS as matrix; moreover, photoactivation time for RTP production is also greatly shortened. Three N‐arylcarbazole derivatives are employed as dopants and afford the same regular results, and the afterglow lifetime of RTP elastomer is up to 1.22 s. Since the general rubbers such as polyisoprene are ineffective doping matrices and PS is not good matrix, the interface phase of polyphase polymers plays an important role in promoting and stabilizing triplet‐state emission. Based on the different confined environments in various phase regions for organic dopants, a new stabilizing RTP mechanism is discussed to understand the unique stabilizing RTP effect of multiphase matrices. This study not only develops a high‐performance RTP elastomer but also discloses a fresh strategy for enhancing RTP of organic‐doped polymers.